Quantitative Studies on Fabrics as Disseminators of Viruses: V. Effect of Laundering on Poliovirus-Contaminated Fabrics - Sidwell, Robert W. (1971)
The effects of laundering with both anionic and nonionic detergents in cold, warm, and hot water on poliovirus-contaminated cotton sheeting, cotton terry cloth, washable wool shirting, wool blanketing, dull nylon jersey, and dacron/cotton shirting were determined. The fabrics were exposed to virus by aerosolization and direct contact (pipette) in separate studies. Although the results varied with each factor used in the study, virus titers on all the fabrics were generally reduced considerably by the laundering process. When the fabrics were dried for 20 hr after laundering, an additional decline in virus titers was seen, often to below detectable levels. The type of detergent used made little difference in effect on virus titer reduction, but the hot wash water markedly reduced the detectable virus. Fabric type was not a major factor in the majority of the experiments, although virus tended to be eliminated more readily from the nylon jersey, and in warm water the virus persisted longer on wool blanketing material laundered in anionic detergent. Sterile fabrics of each type laundered with similar fabrics which contained virus often became contaminated by the virus during the laundering process. Virus titers ranging from undetectable to 10(3.9) cell culture 50% infectious doses/ml were obtained from samples of the rinse water after warm- and cold-water laundering.